The 13-minute murder : thrillers - Patterson, James, 1947-; Farnsworth, Christopher; DiLallo, Max; Serafin, Shan, 1982-; Patterson, James, 1947-; Patterson, James, 1947- (2019)
Dead man running: Psychiatrist Randall Beck specializes in PTSD cases--and his time is limited. Especially when he uncovers a plot to kill a presidential candidate.
113 minutes: Molly Rourke's son has been murdered--and she knows who's responsible. Now she's taking the law into her own hands. Never underestimate a mother's love.
The 13-minute murder: Micheal Ryan can kill anybody in just minutes--from the first approach to the clean escape. His skills have served him well, and he has a grand plan: to get out alive and spend his earnings with his beloved wife, Maria. An anonymous client offers Ryan a rich payout to assassinate a target in Harvard Yard. It's exactly the last big job he needs to complete his plan. The precision strike starts perfectly, then somehow explodes into a horrifying spectacle. Ryan has to run and Maria goes missing. Now the world's fastest hit man sets out for one last score: Revenge. And every minute counts.
Dead man running / James Patterson with Christopher Farnsworth -- 113 minutes / James Patterson with Max DiLallo -- The 13-minute murder / James Patterson with Shan Serafin.
Dead Man Running originally published in an ebook edition, September 2017.
113 Minutes originally published in trade paperback and ebook editions, September 2016.
Keywords: Assassins -- Fiction; Murder -- Fiction; Sons -- Death -- Fiction; Mothers -- Fiction; Revenge -- Fiction; Thrillers (Fiction); Novellas